Government regulations, external financing, and economic performance: The case of Chile - Uwe Corsepius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
Most Latin American countries relied to a large extent on foreign funds to finance their economic development in the seventies and eighties. However, important differences existed with respect to the structure of their capital inflows, the regulations affecting different types of inflows and their overall economic performance. The relative importance of debt finance and foreign direct investments (fdi) in total external liabilities differed significantly between major Latin American borrowers, such as Brazil, Chile and Mexico. In Chile, fdi accounted for only 12 per cent of total external liabilities in 1973 while the ratios were 37 and 23 per cent for Brazil and Mexico respectively (Appendix Table A3). On the other hand, it was only in Chile that the stock of fdi increased relative to total debt outstanding recently.
Keywords: 330